2017
DOI: 10.1038/cddis.2017.34
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of autophagy blocks cathepsins–tBid–mitochondrial apoptotic signaling pathway via stabilization of lysosomal membrane in ischemic astrocytes

Abstract: Our previous study and others have demonstrated that autophagy is activated in ischemic astrocytes and contributes to astrocytic cell death. However, the mechanisms of ischemia-induced autophagy remain largely unknown. In this study, we established a rat's model of permanent middle cerebral artery occlusion (pMCAO) and an in vitro oxygen and glucose deprivation (OGD) model. Autophagy was inhibited by either pharmacological treatment with 3-methyladenine (3-MA) and wortmannin (Wort) or genetic treatment with kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 56 publications
2
51
0
Order By: Relevance
“…However, it has also been reported that different mechanisms to inhibit autophagy also protect against myocardial ischemia/reperfusion injury (Wu et al, 2018;Yu et al, 2018). It has been found that application of 3-MA to inhibit autophagy alleviates astrocyte injury by inhibiting LMP (Zhou et al, 2017). In the present study, we also observed that 3-MA treatment and ATG5 siRNA improved cardiomyocyte resistance against OGD stress and inhibited LMP, whereas application of CQ to impede autophagic flux further exacerbated LMP.…”
Section: Discussionsupporting
confidence: 72%
“…However, it has also been reported that different mechanisms to inhibit autophagy also protect against myocardial ischemia/reperfusion injury (Wu et al, 2018;Yu et al, 2018). It has been found that application of 3-MA to inhibit autophagy alleviates astrocyte injury by inhibiting LMP (Zhou et al, 2017). In the present study, we also observed that 3-MA treatment and ATG5 siRNA improved cardiomyocyte resistance against OGD stress and inhibited LMP, whereas application of CQ to impede autophagic flux further exacerbated LMP.…”
Section: Discussionsupporting
confidence: 72%
“…All these studies revealed that autophagy plays neuroprotective roles after cerebral I/R injury. Reports also demonstrate that autophagy is deleterious for ischemic brain (Zhou et al, 2017;Feng et al, 2018). This discrepancy might be caused by different animal strains, ischemic models, and time of ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence strongly indicates that ALP is induced in multiple ischemic stroke models as reflected by the accumulation of autophagosomes and activation of lysosomal function [1,2,6,7]. However, it is noteworthy that ischemic injury can trigger a defect in ALP by causing lysosomal dysfunction, thus resulting in the abnormal accumulation of autophagosomes and substrates [8][9][10][11][12]. In a 2vessel occlusion (2-VO) ischemic stroke model, treatment with chloroquine (CQ) does not further change the LC3-II levels, suggesting that ALP is impaired [8].…”
Section: Introductionmentioning
confidence: 99%